Cardinal points : poems - Pettit, Michael (Iowa City : University of Iowa Press, 1988)
Strung throughout the book are poems based on the Scottish photographer Eadwaerd Muybridge's Animal Locomotion, a historic photographic document. Pettit uses these pioneering images as the basis for his poetic dreaming, and the result is a poignant, integrated sequence of highly moving poems, studded between other vivid lyrics.
Woman jumping from rock to rock -- Sunday stroll -- Evening on a Canadian lake -- Pavlov's dog -- So long, Tuscaloosa -- The flight path -- Man performing back somersault -- Men wrestling -- No birds -- Sparrow of española -- The uncompahgre range -- Many Buddhists -- Mighty Sebastian Bach -- Los Alamos rush hour -- Sparrow Rousant -- The beyond -- Elderly man lifting log -- Woman turning and lifting train -- Driving lesson -- Virginia evening -- Home again -- Louisiana new year -- National geographic -- Woman emptying bucket of water on seated companion -- Man walking downstairs backwards, turning, walking away while carrying rock -- Willows -- Astral life -- Valentine show at the lingerie shop -- Petting zoo -- March thaw -- House move -- Legless boy climbing in and out of chair -- Man shadowboxing -- Bad back -- The fox hunt -- Furnace without end -- Boat-tailed grackles -- Footsteps -- Star route, box 2 -- Full cry -- Girl walking towards woman, carrying flower -- Cardinal points.
Series statement from jacket.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: American poetry; Poésie américaine.; POETRY -- American -- General; American poetry; American poetry